2022
DOI: 10.1182/bloodadvances.2021006001
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation at the CXCR5 gene locus limits trafficking potential of CD8+ T cells into B-cell follicles during HIV-1 infection

Abstract: CD8+ T-cells play an important role in HIV control. However, in human lymph nodes (LNs), only a small subset of CD8+ T-cells expresses CXCR5, the chemokine receptor required for cell migration into B cell follicles, which are major sanctuaries for HIV persistence in individuals on therapy. Here, we investigate the impact of HIV infection on follicular CD8+ T-cells (fCD8s) frequencies, trafficking pattern and CXCR5 regulation. We show that, although HIV infection results in a marginal increase of fCD8s in LN, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…5g ). These data are consistent with our recent publication where we showed by IF imaging that CD8 + T cells are largely excluded from GCs 44 . These data partly explain the observed greater HIV antigen burden in GCs relative to extrafollicular areas in some donors.…”
Section: Resultssupporting
confidence: 94%
“…5g ). These data are consistent with our recent publication where we showed by IF imaging that CD8 + T cells are largely excluded from GCs 44 . These data partly explain the observed greater HIV antigen burden in GCs relative to extrafollicular areas in some donors.…”
Section: Resultssupporting
confidence: 94%
“…Lymph nodes (LN), peripheral blood mononuclear cells (PBMC), and plasma (PL) samples were collected from individuals infected with HIV-1 subtype C from three cohorts in Durban, South Africa: the HIV Pathogenesis Programme acute infection cohort ( Radebe et al, 2011 ), the “Females Rising through Education, Support and Health” (FRESH) cohort ( Ndhlovu et al, 2015 ) and the Lymph Node cohort ( Ogunshola et al, 2022 ). Study participants were chosen based on the availability of LN samples and the availability of PBMC and PL samples that were collected close to the LN excision time point.…”
Section: Methodsmentioning
confidence: 99%
“… Strategies for targeting CXCR5 + CD8 + T cells in immunotherapies against HIV infection. (A) Adoptive transfer of ex vivo expanded endogenous CXCR5 + CD8 + T cells with anti-PD-1 or anti-PD-L1 blocking antibodies or CXCR5 + CD8 + T cell-promoting cytokines, e.g., IL-15 super agonist ( Miller et al, 2022 ), recombinant IL-2 ( Codarri Deak et al, 2022 ; Perdomo-Celis et al, 2022 ), GSK3 inhibitor ( Perdomo-Celis et al, 2022 ), recombinant TGF- ß ( Ogunshola et al, 2022 ), overexpressed CXCR5 ( Ayala et al, 2017 ) and TCF1 ( Rutishauser et al, 2021 ) and using the CXCR5 expressed CAR-T ( Pampusch et al, 2022 ). (B) ART with anti-PD-1 or anti-PDL1 blocking antibodies combined with CXCR5 + CD8 + T cell-promoting cytokines, e.g., IL-15 super agonist ( Miller et al, 2022 ) and IL-2 ( Codarri Deak et al, 2022 ; Perdomo-Celis et al, 2022 ) in vivo .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A recent study found that CXCR5 – CD8 + T cells have closed chromatin at the cxcr5 transcriptional start site, in vitro culture with recombinant TGF-ß significantly increased CXCR5 expression. However, the detailed mechanism is still unknown ( Ogunshola et al, 2022 ). Thus, Id2, E2A, Tcf1, Bcl6, and Blimp1 form a transcriptional loop to regulate the CXCR5 expression and T FC cell generation in mice.…”
Section: Introductionmentioning
confidence: 99%